2021
DOI: 10.1016/j.ejmech.2021.113446
|View full text |Cite
|
Sign up to set email alerts
|

AAA ATPases as therapeutic targets: Structure, functions, and small-molecule inhibitors

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 156 publications
1
21
0
Order By: Relevance
“…RuvBL1 (synonyms: Pontin52, Rvb1, TAP54a, and TIP49) is a highly conserved ATPase of the AAA+ (ATPases Associated with various cellular Activities) superfamily, and possesses intrinsic ATPase activities and DNA helicase activities (14)(15)(16). It is involved in various cellular processes, such as transcription, DNA damage, cellular transformation and cancer metastasis (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…RuvBL1 (synonyms: Pontin52, Rvb1, TAP54a, and TIP49) is a highly conserved ATPase of the AAA+ (ATPases Associated with various cellular Activities) superfamily, and possesses intrinsic ATPase activities and DNA helicase activities (14)(15)(16). It is involved in various cellular processes, such as transcription, DNA damage, cellular transformation and cancer metastasis (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…These amino acids play important roles in the binding and hydrolysis of ATP (Fig. 4e) (Yedidi et al, 2017; Zhang et al, 2021; Zhang and Mao, 2020). Indeed, when these mutations were introduced, not only the disaggregase activity was abolished, but the ATPase activity was significantly impaired (Warren et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…ATAD2 can be divided into four regions, N-terminal acidic domain, AAA ATPase domain (AAA-ATAD2), bromodomain, and C-terminal domain ( Figure 1 ). AAA-ATAD2 contains Walker A, Walker B, sensor 1, sensor 2, and an arginine finger and functions as a hexameric compound [ 7 ]. The bromodomain has four α-helix bundles and ZA and BC loops between the two helices, which contain several amino acids necessary to interacting with acetylated lysines to form a hydrophobic pocket [ 71 ].…”
Section: Atad2 Is a Member Of Bromodomain-containing Proteinsmentioning
confidence: 99%
“…There are two isoforms of human ATAD2 , known as ATAD2A and ATAD2B [ 4 ], and most published functional studies have been done on ATAD2/ATAD2A; hence, ATAD2 is also the focal point of our review. ATAD2 is mainly expressed in male genital cells [ 5 ] and has two conserved protein domains, AAA ATPase and bromodomain (BRD), which are the main structures for its biological functions [ 6 , 7 ]. Studies have shown that ATAD2 acts as an epigenetic decoder and transcription factor or coactivator involved in many cellular processes, such as DNA replication [ 8 ], transcriptional regulation [ 9 ], protein modification [ 10 ], and cell proliferation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%